Citation analysis of scientific categories. Issue 5 (May 2017) - Patience, Gregory S.; Patience, Christian A.; Blais, Bruno; Bertrand, Francois
Abstract: Databases catalogue the corpus of research literature into scientific categories and report classes of bibliometric data such as the number of citations to articles, the number of authors, journals, funding agencies, institutes, references, etc. The number of articles and citations in a category are gauges of productivity and scientific impact but a quantitative basis to compare researchers between categories is limited. Here, we compile a list of bibliometric indicators for 236 science categories and citation rates of the 500 most cited articles of each category. The number of citations per paper vary by several orders of magnitude and are highest in multidisciplinary sciences, general internal medicine, and biochemistry and lowest in literature, poetry, and dance. A regression model demonstrates that citation rates to the top articles in each category increase with the square root of the number of articles in a category and decrease proportionately with the age of the references: articles in categories that cite recent research are also cited more frequently. The citation rate correlates positively with the number of funding agencies that finance the research. The category h -index correlates with the average number of cites to the top 500 ranked articles of each category ( R 2 = 0.997 ). Furthermore, only a few journals publish the top 500 cited articles in each category: four journals publish 60% ( σ = ± 20 % ) of these and ten publish 81% ( σ = ± 15 % ).